Revolutionizing cancer immunotherapy: unleashing the potential of bispecific antibodies for targeted treatment - Guo, Xiaohan; Wu, Yi; Xue, Ying; Xie, Na; Shen, Guobo (Frontiers in Immunology, 2023)
Recent progressions in immunotherapy have transformed cancer treatment, providing a promising strategy that activates the immune system of the patient to find and eliminate cancerous cells. Bispecific antibodies, which engage two separate antigens or one antigen with two distinct epitopes, are of tremendous concern in immunotherapy. The bi-targeting idea enabled by bispecific antibodies (BsAbs) is especially attractive from a medical standpoint since most diseases are complex, involving several receptors, ligands, and signaling pathways. Several research look into the processes in which BsAbs identify different cancer targets such angiogenesis, reproduction, metastasis, and immune regulation.By rerouting cells or altering other pathways, the bispecific proteins perform effector activities in addition to those of natural antibodies. This opens up a wide range of clinical applications and helps patients with resistant tumors respond better to medication. Yet, further study is necessary to identify the best conditions where to use these medications for treating tumor, their appropriate combination partners, and methods to reduce toxicity. In this review, we provide insights into the BsAb format classification based on their composition and symmetry, as well as the delivery mode, focus on the action mechanism of the molecule, and discuss the challenges and future perspectives in BsAb development.